THE EFFECT OF SERVICE QUALITY AND FACILITIES ON LOYALTY MEDIATED BY OUTPATIENT PATIENT SATISFACTION AT DR. M. THOMSEN NIAS REGIONAL HOSPITAL - Nazara, Visensius Kurniel; Haryono, Budi (PT. Hafasy Dwi Nawasena, 2025)
In the increasingly competitive hospital industry, increasing patient satisfaction through quality of service and facilities is an important aspect in maintaining patient loyalty. This study aims to determine the effect of service quality and facilities on patient loyalty mediated by outpatient satisfaction at Dr. M. Thomsen Nias Regional General Hospital. The population of this study was all 135 outpatients at Dr. M. Thomsen Nias Regional General Hospital. The sample size was determined using the Slovin formula with a 5% error rate, resulting in a sample size of 100 respondents. The results of this analysis indicate that all indicators used in this study are valid and reliable. The results show that service quality and facilities have a positive and significant effect on patient satisfaction. Furthermore, patient satisfaction is also proven to have a positive and significant effect on patient loyalty. In addition, service quality and facilities indirectly affect loyalty through the mediating variable of patient satisfaction. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant effect.